Huperzine A versus epicatechin: a comparative study of their potential protective effect on lipopolysaccharide-induced lung injury in mice - Tariq, Zeena Thamir; Abu-Raghif, Ahmed R.; Raheem, Abdulla K.; Ridha-Salman, Hayder; Abbas, Alaa Hamza; Zigam, Qassim A.; Abbas, Weaam J.; AbdulAemah, Maytham Ahmed; Abbas, Hasanain A. M.; Al-Athari, Ali Jihad Hemid; et al. (Pharmakeftiki, 2025)
A cytokine storm is a severe and potentially fatal condition resulting from an excessive immune response. Epicatechin and huperzine A have demonstrated anti-inflammatory and antioxidant properties, suggesting their potential utility in mitigating tissue damage and cytokine storm severity. This study aimed to compare the protective effects of huperzine A and epicatechin in a cytokine storm-like murine model. Sixty male Swiss albino mice were randomly allocated into six groups. Except for the control group, all animals received a single intraperitoneal injection of lipopolysaccharide (LPS; 5 mg/kg) in order to induce a cytokine storm. The induction group received LPS without further intervention. The remaining groups were pre-treated for three consecutive days prior to LPS administration as follows: vehicle group (1% dimethyl sulfoxide), methylprednisolone group (50 mg/kg/day methylprednisolone), huperzine A group (0.2 mg/kg/day huperzine A), and epicatechin group (25 mg/kg/day epicatechin). The histological analysis of lung tissues and the quantification of serum cytokines – interleukin-1 beta (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α) – revealed that all pre-treated groups exhibited significant anti-inflammatory effects. Notably, epicatechin conferred a more pronounced protective effect than either methylprednisolone or huperzine A, as evidenced by reduced pulmonary histopathological alterations and lower serum cytokine concentrations. In conclusion, both huperzine A and epicatechin demonstrated protective efficacy against the LPS-induced cytokine storm, with epicatechin showing superior performance in attenuating systemic inflammation and lung injury.